Mapping the Knowledge Structure and Research Trends of Organisational Embeddedness and Turnover Intention: A Bibliometric and Visualisation Analysis (2010–2025) - Xie, Qingling; Yakub, Nur Asyikin; Mahmud, Norashikin; Abdul Hanid, Mohd Fadzil (International Review of Management and Marketing, 2026)
Employee retention has become a key concern in organisational management and human resource policy discussions because turnover affects workforce stability, service continuity and institutional capacity. Yet research on why employees remain attached to organisations and how this attachment relates to turnover intention remains fragmented across management, psychology, healthcare, hospitality and public-sector studies. This review maps the knowledge structure of research connecting organisational embeddedness and turnover intention between 2010 and 2025. Using 42 Scopus-indexed peer-reviewed publications, the study combines descriptive bibliometric indicators, metadata harmonisation and keyword co-occurrence visualisation. The results show a small but identifiable research domain, with journal-based publication, concentrated citation influence and recurring themes around job embeddedness, organisational fit, social ties, perceived sacrifice, job satisfaction, trust and work-related shocks. The field is shaped mainly by job embeddedness theory, conservation of resources theory and social exchange theory, but empirical designs remain dominated by cross-sectional surveys. The review identifies three future directions: stronger longitudinal and multilevel designs, closer attention to digital and hybrid work contexts, and more explicit cross-cultural and sectoral comparisons. By clarifying how organisational embeddedness has been studied as a retention mechanism, the article offers a basis for more cumulative research on employee mobility and context-sensitive retention practice.